The Cheating Heart: Phenomenology in Women Who Decides to Have an Affair in Marriage - Rinanda Rizky Amalia Shaleha (Jurnal Psikologi, 2021)
Infidelity in marriage is a complex process. People have different reasons for deciding to have a relationship outside of marriage. This study aims to investigate the reasons of married women for having marital infidelity and explore the risk factors that cause it. This research was conducted using a qualitative approach with phenomenology as the method. Three women who have had marital infidelity are willing to be subjects in this study. Data was collected by using open interview and observation methods. As a result, failed conflict resolution, different communication styles, low-quality time, low intimacy, unfulfilled expectations from partners, and the absence of protective factors are factors that cause women to have an affair.